Desentralisasi Asimetris dan Desain Konstitusional Paradiplomasi Pemerintah Provinsi Sulawesi Utara dalam Tata Kelola Perbatasan Asia Pasifik - Josepus Julie Pinori; Donna Okthalia Setiabudhi; Toar Kamang Ronald Palilingan (Jurnal Hukum Lex Generalis, 2026)
This article examines the implementation of asymmetric decentralization and the constitutional design of the North Sulawesi Provincial Government’s paradiplomacy in Asia-Pacific border governance through normative legal research. The findings indicate that North Sulawesi’s strategic position as a border region requires a more adaptive distribution of authority. However, the centralization of foreign affairs powers continues to limit regional paradiplomatic initiatives. Therefore, strengthening the constitutional framework is necessary to support coordinated economic cooperation, security, and border area development within the framework of the Unitary State of the Republic of Indonesia.